2013
DOI: 10.1021/ol4030259
|View full text |Cite
|
Sign up to set email alerts
|

Chelation-Controlled Additions to α-Silyloxy Aldehydes: An Autocatalytic Approach

Abstract: The Felkin-Anh model has been widely accepted to describe stereochemical outcomes in nucleophilic additions to α-silyloxy carbonyl compounds. Herein, it is demonstrated that chelation-controlled additions can be performed using dialkylzinc reagents in the presence of chlorotrimethylsilane with good to excellent diastereoselectivities. Ethyl zinc chloride, the Lewis acid responsible for promoting chelation, is generated in situ in an autocatalytic fashion. This approach circumvents its use in stoichiometric amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The desired transformation required formation of metal vinyl species 25 generated from vinyl iodide 2 to add to β-azido ketone 3 in a diastereoselective fashion by chelation to the α-alkoxy group ( 27 to 28 ) to finally access alcohol 26 . 10 Extensive screening and reaction optimization 29 revealed that the addition proceeded in high yield and remarkable diastereoselectivity when dimethylzinc 30 was used to generate vinyl zincate complex 25 as the precursor for the chelation-controlled addition. The success of the zincate addition highly depends on the quality of the organometallic reagent employed, and the reaction temperature must be kept rigorously under −50 °C in order to avoid decomposition of ketone 3 .…”
mentioning
confidence: 99%
“…The desired transformation required formation of metal vinyl species 25 generated from vinyl iodide 2 to add to β-azido ketone 3 in a diastereoselective fashion by chelation to the α-alkoxy group ( 27 to 28 ) to finally access alcohol 26 . 10 Extensive screening and reaction optimization 29 revealed that the addition proceeded in high yield and remarkable diastereoselectivity when dimethylzinc 30 was used to generate vinyl zincate complex 25 as the precursor for the chelation-controlled addition. The success of the zincate addition highly depends on the quality of the organometallic reagent employed, and the reaction temperature must be kept rigorously under −50 °C in order to avoid decomposition of ketone 3 .…”
mentioning
confidence: 99%
“…The high diastereoselectivities in Scheme 7 suggest that this approach should be appropriate to a host of related aldehydes. Further studies led to development of an autocatalytic version of this reaction, 42 which is covered elsewhere.…”
Section: Highly Diastereoselectivementioning
confidence: 99%
“… 2 , 6 We recently demonstrated, however, that a remarkable class of Lewis acids, RZnX (X = halide or OSO 2 R), promotes the addition of a wide range of alkyl and vinyl organozinc reagents to α- and β-silyloxy aldehydes and ketones via chelation control with very high diastereomeric ratios (Scheme 1 B). 7 …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that α- and β-silyloxy aldehydes and ketones react with nucleophiles via the Felkin–Anh pathway with few exceptions (Scheme A). , We recently demonstrated, however, that a remarkable class of Lewis acids, RZnX (X = halide or OSO 2 R), promotes the addition of a wide range of alkyl and vinyl organozinc reagents to α- and β-silyloxy aldehydes and ketones via chelation control with very high diastereomeric ratios (Scheme B) …”
Section: Introductionmentioning
confidence: 99%